KEPEMIMPINAN VISIONER KEPALA SEKOLAH MENENGAH KEJURUAN DARUSSALAM BLOKAGUNG TEGALSARI BANYUWANGI - Muhammad Alaika Nasrulloh; Rahmadhani Lailiya (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2021)
The purpose of this study was to determine the visionary leadership of the head of the vocational high school Darussalam Blokagung Banyuwangi. This study uses a qualitative approach (Qualitative Research). The technique of validating data through interviews, observation, and documentation (Triangulation) to examine related phenomena in the triangulation perspective include several compnen namely triangulation techniques and data sources. Type of case study research. The visionary leadership of the head of the vocational high school Darussalam uses 4 roles incluiding direction setterrs, coaches and mentors, change of agent, spokespersons. Supporting factors get support from the islamic boarding school of foundation Darussalam, work enthusiasm from educators and vocational education staff, enthusiasm for learning for vocational school students. Inhibiting factors include the lack of human resources for teacher and school employees, the geographical location of vocational high school , lack of disipline for teachers who still come late, student vocational high school lack entehusiasm for learning, discipline and lack of obedience to school qanuns.